A phase Ib/II study of modakafusp alfa alone and in combination with pembrolizumab in patients with advanced or metastatic solid tumors - Gill, David; Cowey, Charles L.; Daniels, Gregory A.; Sommerhalder, David; Abdul-Karim, Raghad; Kirkwood, John M.; Kolodney, Joanna; Mehmi, Inderjit; Roberts-Thomson, Rachel; Strauss, James; Thomas, Sajeve; Whitman, Eric; et al. (Frontiers in Oncology, 2025)
BackgroundModakafusp alfa is a novel immunocytokine comprising two attenuated interferon-α2b molecules fused to an anti-CD38 IgG4 monoclonal antibody. Modakafusp alfa has shown immune cell activation and antitumor activity in preclinical mouse models, including in combination with an anti-programmed cell death (PD-1) receptor in tumors that do not express CD38, and demonstrated clinical responses and immune activation in patients with relapsed/refractory multiple myeloma.MethodsIn phase Ib, adult patients with advanced/metastatic solid tumors received escalating doses of modakafusp alfa 0.1–1.5 mg/kg intravenously every 3 weeks (Q3W) across six dosing cohorts. In phase II, patients with unresectable/metastatic cutaneous melanoma and resistance to ≤2 anti-PD-1 therapies in the metastatic setting received modakafusp alfa 1 mg/kg Q3W in combination with pembrolizumab Q6W. Primary objectives were to determine the safety/tolerability as a single agent in phase I, and efficacy in combination with pembrolizumab in phase II.ResultsA total of 21 and 24 patients were enrolled across phases Ib and II, respectively. The recommended phase II dose of modakafusp alfa was 1 mg/kg. The most common drug-related adverse events were infusion-related reactions (IRRs; 52.4%) and thrombocytopenia (28.6%) in phase Ib; and headache (58.3%), fatigue (54.2%), IRRs (41.7%), neutropenia (37.5%), and nausea (33.3%) in phase II. In phase Ib, seven patients had a best response of stable disease (SD); in phase II, one patient had a confirmed complete response, one had a confirmed partial response, and seven had SD. All immunogenicity-evaluable patients were anti-drug antibodies (ADAs) positive following treatment with modakafusp alfa; neutralizing ADAs were reported in 82.4% and 90.9% of patients in phases Ib and II, respectively, which was associated with drug exposure reduction. Pharmacodynamic analyses demonstrated innate and adaptive immune activation in peripheral blood and within tumors. Paired biopsy analysis revealed two subgroups of patients defined by differences in CD38 upregulation, accompanied by differential intratumoral pharmacodynamic changes. Correlative analysis was inconclusive.ConclusionsModakafusp alfa induces innate and adaptive immune responses, supporting its hypothesized mechanism of action (MoA) in patients with advanced solid tumors. High immunogenicity and the potentially limited treatment effect of the interferon MoA may have contributed to limited efficacy in these patients.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04157517, identifier NCT04157517.